2017
DOI: 10.1128/jcm.00043-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of StrepB Select Chromogenic Medium and the Fast-Track Diagnostics Group B Streptococcus (GBS) Real-Time PCR Assay Compared to Routine Culture for Detection of GBS during Antepartum Screening

Abstract: Life-threatening infection in neonates due to group B Streptococcus (GBS) is preventable by screening of near-term pregnant women and treatment at delivery. A total of 295 vaginal-rectal swabs were collected from women attending antepartum clinics in Calgary, Alberta, Canada. GBS colonization was detected by the standard culture method (Strep B Carrot Broth subcultured to blood agar with a neomycin disk) and compared to recovery with Strep Group B Broth (Dalynn Biologicals) subcultured to StrepBSelect chromoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The Colorex Strep A agar also showed much better overall performance (whether read by a technologist or by the software), compared to routine cultures plated on BAPs, with or without the use of a bacitracin disk, to facilitate screening for GAS. Our findings are consistent with a previous study that reported superior performance of chromogenic agar and PCR, compared to routine culture, for recovering group B Streptococcus (13). In addition, our previous study on the Lyra PCR assay detected GAS in an additional 26 specimens that were culture negative (10).…”
Section: Discussionsupporting
confidence: 93%
“…The Colorex Strep A agar also showed much better overall performance (whether read by a technologist or by the software), compared to routine cultures plated on BAPs, with or without the use of a bacitracin disk, to facilitate screening for GAS. Our findings are consistent with a previous study that reported superior performance of chromogenic agar and PCR, compared to routine culture, for recovering group B Streptococcus (13). In addition, our previous study on the Lyra PCR assay detected GAS in an additional 26 specimens that were culture negative (10).…”
Section: Discussionsupporting
confidence: 93%
“…The lowest rates were observed mainly in some East Asian nations [6,12,13]. The across-country differences may be due to differences in techniques [23][24][25][26][27][28][29][30][31][32][33][34][35]. PCR testing after broth enrichment has been has been shown to be a reliable and is now the standard method for GBS testing [24].…”
Section: Plos Onementioning
confidence: 99%
“…PCR testing after broth enrichment has been has been shown to be a reliable and is now the standard method for GBS testing [24]. However, testing conducted intrapartum may show somewhat lower prevalence rates as compared to antepartum testing [25]. If this is so, then there may be excessive use of intrapartum prophylactic antibiotics to prevent GBS [25].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, this delay in obtaining culture results has led to the standard practice of administering broad-spectrum antibiotics to patients presenting with inflammation without knowing the specific microorganisms present [168][169][170][171]. Recently, the use of advanced molecular microbiological PCR-based techniques was proposed as a solution to these problems [23], as such methods can identify a greater number of microorganisms, including those which may be difficult to culture [78, 139-145, 147-154, 172-174], and the results can be rapidly obtained [23,[175][176][177][178][179][180][181]. Molecular microbiological techniques can also rule out false positives obtained by conventional culture likely due to contamination [126].…”
Section: Detection Of Microbial Burden In Amniotic Fluid By 16s Rrna mentioning
confidence: 99%